A changing climate: a review of the accommodation and communication methods, for discussing complex, scientific topics, in county extension in Kansas and Oklahoma - Rohling, Katie (Kansas State University, 2016)
The purpose of this study was to determine specific communication accommodations used by county agricultural and natural resource agents/educators when discussing complex, scientific topics like climate change. Four research objectives were used to determine 1) background and experience of agents/educators, 2) how agents/educators are communicating on complex, scientific topics, 3) climate-change information received and preferred method of receiving future training, and 4) agents’/educators’ communication adjustment. This study was guided by Communication Accommodation Theory to understand how agents/educators are adjusting their communication when speaking to producers with varying education levels, grammar usage, and seeking different types of climate information. This study utilized a mixed method, quantitative and qualitative, survey (n = 42). Extension in Kansas and Oklahoma had not publicized an organizational stance on climate change. Kansas agents and Oklahoma educators had access to climate-change information through a variety of internal and external sources. Agents/educators had a strong background in agriculture and varying ranges of experience in the position. The main communication channel producers utilized to contact agents/educators was the telephone (52.24%). Both states indicated they are conducting an average of five on-farm visits a month. Over half (25) of agents/educators indicated they had received some form of climate-change information since becoming an agent/educator. Agents/educators indicated they received this information from sources external to Extension in Kansas and Oklahoma. They also indicated future training should be interactive and close to home. This study found agents/educators are accommodating in their responses to agricultural producers’ requests for climate-change information, but also showed nonaccommodating tendencies. Agents/educators were viewed as nonaccommodating when they used improper grammar, improper email format, or told the producer there was no need for concern on their perceived climate issue. Agents/educators offered to make site visits to the producers’ field, referred to specialists, and worked to establish credibility. This study determined agents/educators have the background and information sources to adequately and effectively answer producers’ questions about climate change. It was determined the reason agents/educators do not want climate-change conversations is because of a lack of formal training on the matter, and they do not feel comfortable. This study recommends Extension provide communication and climate-change training for agents/educators. It also recommends agents/educators continue to conduct on-farm visits as they are vital to interpersonal communication with agricultural producers. Extension should take steps to reach a younger audience and help young people become involved in agriculture.
Keywords: Communication accommodation theory; Climate change; Agricultural producers; Training; AdaptationExtension communication